EVALUASI PROSEDUR PENGGAJIAN PADA KANTOR DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN SUMBA BARAT DAYA PROVINSI NUSA TENGGARA TIMUR - Elisabet Anastasia Sara Pate; Bambang Budi Prayitno; Lis Lestari S. (Akubis : Jurnal Akuntansi dan Bisnis, 2020)
The purpose of this study is to determine the suitability ofthe Payroll procedure in Revenue Financial Management andDistrict Asset service office in Southwest Sumba regency ofEast Nusa Tenggara province with Government RegulationNo. 7 of 1977 about the Rules of Civil Affairs Officer Payroll.The data collection method is using documentation andinterviews at the Revenue Financial Management andDistrict Asset service office in Southwest Sumba regency ofEast Nusa Tenggara province. The type of this research is acase study to give a detailed overview on the status of theresearch subject, the properties and characters typical ofcases.The results of the payroll procedures evaluation in theRevenue Financial Management and District Asset serviceoffice in Southwest Sumba regency of East Nusa Tenggaraprovince is quite effective, the remuneration procedures arein accordance with Government Regulation No. 7 of 1977regarding regulation of civil service payroll. But theprocedure DPPKAD office salaries, paychecks have not beenincluded and archiving in the relevant sections is stillincomplete. The results of the analysis on the attendance ofcivil servants need an additional column to show the positionof employee positions in government agencies, and thereneeds to be recaps the attendance list as the basis forcalculating the presence of civil servants in the discharge ofeveryday assignment that helps in terms of promotion andadvancement.